Considerantions on Suspension of the Individual Labor Contract - MARA, Teodor (Journal of Legal Studies, 2016)
The article examines the concept of suspension of the individual labor contract of Law no. 53/2003 (Labor Code) as amended and supplemented by June 2015 and the effects of suspension according to legal provisions in force.